Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s13105-016-0520-6
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking myotubularin-related protein 14 show accelerated high-fat diet-induced lipid accumulation and inflammation

Abstract: The phosphoinositide phosphatase, myotubularin-related protein 14 (MTMR14), has been reported to play an important role in the regulation of muscle performance, autophagy, and aging in mice. We previously showed that MTMR14-knockout (KO) mice gain weight earlier than their wild-type (WT) littermates even on a normal chow diet (NCD), suggesting that this gene might also be involved in regulating metabolism. In the present study, we evaluated the effect of MTMR14 deficiency on high-fat diet (HFD)-induced obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Lv et al [12] showed that MTMR14 deficiency led to late-onset inflammation. Consistent with this, mice lacking MTMR14 showed accelerated lipid accumulation and inflammation induced by high-fat diet [13]. Furthermore, it was also reported that MTMR14 knockdown promoted apoptosis in liver cancer cells [14].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Lv et al [12] showed that MTMR14 deficiency led to late-onset inflammation. Consistent with this, mice lacking MTMR14 showed accelerated lipid accumulation and inflammation induced by high-fat diet [13]. Furthermore, it was also reported that MTMR14 knockdown promoted apoptosis in liver cancer cells [14].…”
Section: Discussionsupporting
confidence: 65%
“…A previous study reported that MTMR14 deficiency resulted in metabolic dysfunction and late-onset inflammation [12]. Consistently, the depletion of MTMR14 accelerated high-fat diet-induced inflammation and lipid accumulation in mice [13]. It has also been found that MTMR14 knockdown inhibits migration and promotes apoptosis in liver cancer cells [14].…”
Section: Introductionmentioning
confidence: 72%
“…z < − 2 predicts a downregulation within a gene set associated with a canonical pathway or a transcriptional regulator. iNOS inducible nitric oxide synthase, RXR retinoid X receptor, MIF macrophage migration inhibitory factor, LXR liver X receptor, LPS lipopolysaccharide, APP amyloid protein precursor, EGR1 early growth response protein 1 [43]. FOS, a transcription factor involved in myeloid differentiation [44], was induced by apabetalone treatment to a lesser extent in DM2 + CVD cells compared to control monocytes (Fig.…”
Section: Apabetalone Abolishes "Hyperactive" Gene Expression In Monocmentioning
confidence: 95%
“…MTMR14 was first identified as a phosphatase specific to skeletal and cardiac muscle 12 . It has been reported to be a muscle-specific component, and lifelong MTMR14 deficiency in humans has been implicated in centronuclear myopathy 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, MTMR14 knockdown promotes apoptosis and inhibits migration in liver cancer cells 7 . Studies have also demonstrated that mice lacking MTMR14 show accelerated highfat diet-induced lipid accumulation and inflammation 12 . At the molecular level, MTMR14 specifically dephosphorylates phosphatidylinositol 3,5-biphosphate (PtdIns (3,5)P2) and phosphatidylinositol 3-phosphate (PI3P), which are two of the seven phosphoinositides found in eukaryotic cell membranes 13 .…”
Section: Introductionmentioning
confidence: 99%